Aus: 3. Bilderserie für den Zirkel zum Studium der gesellschaftlichen Rolle der FDJ im Kampf um Einheit und Frieden
Aus: 3. Bilderserie für den Zirkel zum Studium der gesellschaftlichen Rolle der FDJ im Kampf um Einheit und Frieden.